(untitled) (International Journal of Irrigation and Water Management, 2022)
The rain fed crop is highly dependent on environmental conditions, and study aims to evaluate the agronomic performance, yield components and agricultural productivity of six maize cultivars in the region of the coastal tablelands of Alagoas State, Brazil. The experimental design was randomized complete block, with five replications and six treatments. Six maize cultivars, three varieties (Jaboatão, Batité and AL Bandeirante) and three hybrids (AG 7098, AG 7088 and AG 8677) were evaluated from June 8 to October 14, 2015. The experimental area of 2000 m2 (0.2 ha) was divided into six cultivation rows of seven meters linear portions; spaced 0.8 m between rows and 0.25 m between plants, totaling 50.000 plants ha-1. During the experiment, the following were evaluated: plant height, leaf area index (LAI), culm diameter and at the end of the experiment, the production components, agricultural productivity, water balance and the grains water content were determined. The highest grain yield was obtained by hybrid AG 8677 (4.2 t ha-1) followed by the AG 7098 (3.6 t ha-1), with an average of 3.0 t ha-1 for all cultivars. Variety AL Bandeirante achieved a productivity similar to that of hybrid AG 7088. The lowest productivities were verified by varieties Jaboatão (2.0 t ha-1) and Batité (2.2 t ha-1). However, these yields were statistically similar to that of variety AL Bandeirante. The maximum water excess during cultivation of maize was 504 mm. An increased productivity was shown by hybrid AG 8677, and the smallest of the range was the variety Jaboatão. The average productivity of the hybrids was 50% higher than that of the varieties.